Possible Role of NADPH Oxidase 4 in Angiotensin II-Induced Muscle Wasting in Mice - Kadoguchi, Tomoyasu; Shimada, Kazunori; Koide, Hiroshi; Miyazaki, Tetsuro; Shiozawa, Tomoyuki; Takahashi, Shuhei; Aikawa, Tatsuro; Ouchi, Shohei; Kitamura, Kenichi; Sugita, Yurina; Hamad, Al Shahi; Kunimoto, Mitsuhiro; et al. (Frontiers in Physiology, 2018)
Background: Muscle wasting is a debilitating phenotype associated with chronic heart failure. We have previously demonstrated that angiotensin II (AII) directly induces muscle wasting in mice through the activation of NADPH oxidase. In this study, we tested the hypothesis that deficiency of NADPH oxidase 4 (Nox4), a major source of oxidative stress, ameliorates AII-induced muscle wasting through the regulation of redox balance. Methods and Results: Nox4 knockout (KO) and wild-type (WT) mice were used. At baseline, there were no differences in physical characteristics between the WT and KO mice. Saline (vehicle, V) or AII was infused via osmotic minipumps for 4 weeks, after which, the WT + AII mice showed significant increases in NADPH oxidase activity and NOX4 protein compared with the WT + V mice, as well as decreases in body weight, gastrocnemius muscle weight, and myocyte cross-sectional area. These changes were significantly attenuated in the KO + AII mice (27 ± 1 vs. 31 ± 1 g, 385 ± 3 vs. 438 ± 13 mg, and 1330 ± 30 vs. 2281 ± 150 μm2, respectively, all P < 0.05). The expression levels of phospho-Akt decreased, whereas those of muscle RING Finger-1 and MAFbx/atrogin-1 significantly increased in the WT + AII mice compared with the WT + V mice. Furthermore, nuclear factor erythroid-derived 2-like 2 (Nrf2) and the expression levels of Nrf2-regulated genes significantly decreased in the WT + AII mice compared with the WT + V mice. These changes were significantly attenuated in the KO + AII mice (P < 0.05). Conclusion: Nox4 deficiency attenuated AII-induced muscle wasting, partially through the regulation of Nrf2. The Nox4–Nrf2 axis may play an important role in the development of AII-induced muscle wasting.